European integration as an underestimated success programme - Gunther Tichy (WWWforEurope, 2015)
European integration was and is a success programme. It was possible to successfully cope with the challenges of globalisation, to perform better than the United States in international competition, defending the European model of social security and inclusion while keeping pace in terms of per capita growth, and the supranational concentration of bargaining power proved helpful with respect to multinationals as well as in international diplomacy. However, the inevitable lack of vision for the final state of the integration process disturbs the safety-oriented European public and impairs EUs image. There is a search for final, patent solutions based on traditional institutions and models. In this, one overlooks the fact that European integration is a systemic process and an experiment at the end of which something new will presumably have been created. The adaptation and the advancement of the specific European model, based on inalienable human rights (not the least for women), rule of law, separation of powers, freedom of religion, popular sovereignty and representative democracy is indispensable. It is not easy, given differences of assessment of values even with the United States, and the rejection of 'Western' values outside the Western World, in many cases even with considerable aggressiveness.
Keywords: 330